2014
DOI: 10.1002/phy2.198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxic training on inflammatory and metabolic risk factors: a crossover study in healthy subjects

Abstract: The purpose of this study was to investigate the influence of hypoxic physical exercise on metabolic syndrome (MS) risk markers and high‐sensitivity C‐reactive protein (CRP) and to compare its effects on preperitoneal fat, arterial stiffness, and several blood parameters related to MS to those of a control group who trained under normoxic conditions. Fourteen healthy men were examined. Participants performed treadmill exercise 3 days per week for 4 weeks, under either normobaric hypoxic or normobaric normoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…20 In a crossover study by Shi et al involving 4 weeks of aerobic exercise in a 2500-m hypoxic environment for male college students, PWV was signifi cantly lower in the hypoxic group after training. 5 In addition, Nishiwaki et al reported that hypoxic training increased fl ow-mediated vasodilation (FMD) (an indicator of increased blood fl ow) and reduced PWV, similar to the results of this study. 21 Katayama et al reported that aerobic exercise improved vascular endothelial function to a greater extent in a hypoxic environment than in a sea-level environment.…”
Section: F1 = Difference Between Groups; F2 = Difference Before and Asupporting
confidence: 81%
See 2 more Smart Citations
“…20 In a crossover study by Shi et al involving 4 weeks of aerobic exercise in a 2500-m hypoxic environment for male college students, PWV was signifi cantly lower in the hypoxic group after training. 5 In addition, Nishiwaki et al reported that hypoxic training increased fl ow-mediated vasodilation (FMD) (an indicator of increased blood fl ow) and reduced PWV, similar to the results of this study. 21 Katayama et al reported that aerobic exercise improved vascular endothelial function to a greater extent in a hypoxic environment than in a sea-level environment.…”
Section: F1 = Difference Between Groups; F2 = Difference Before and Asupporting
confidence: 81%
“…Shi et al examined the eff ect of hypoxic training on high-sensitivity C-reactive protein (hs-CRP) levels, an infl ammatory marker, in healthy adult males and reported that hs-CRP levels were signifi cantly lower in the hypoxic group than in the control group after the training. 5 Therefore, hypoxic training may have positive, anti-infl ammatory eff ects on metabolic syndrome-related factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because lean body mass did not change significantly in either group, the reduction of body mass identified after hypoxic training primarily results from the reduction of body fat. Our results also support previous findings that hypoxic exercise training induces reductions of body mass and/or body fat (Haufe et al ., ; Netzer et al ., ; Wiesner et al ., ; Shi et al ., ). Therefore, the present data suggest that exercise training under mild hypoxic conditions could more effectively reduce body fat even in postmenopausal women than exercise training in normoxia.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, several reports have demonstrated that exercise training under mild‐to‐moderate hypoxic conditions (i.e. approximately 2000–2700 m above sea level, 3–4 days week −1 , for 4–8 weeks) induces a reduction of body mass and fat and an increase in insulin sensitivity (Haufe et al ., ; Netzer et al ., ; Wiesner et al ., ; Shi et al ., ). We have also provided evidence that aquatic exercise training [i.e.…”
Section: Introductionmentioning
confidence: 97%